(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article gives an overview of Peronosporales fungi of Kyrgyzstan. The list of fungi with feeding plants is presented. At present, 106 species of representatives from 8 genera of 1 family are registered on the territory of the Republic. These fungi are plant parasites and are registered on 137 species of plants from 104 genera of 27 families. Three species were recorded for the first time for the Republic; Peronospora oerteliana J.G. Kühn - on Anagallis sp., Peronospora vvedenskyi Golovin - on Euclidium syriacum (L.) W.T. Aiton. Aiton., Psuedoronospora urticae urticae (Lib.) E.S. Salmon & Ware- on Urtica dioica L.